Vitamin D3 Levels in Idiopathic Low Backache Women of Child Bearing Age attending Neurosurgery OPD - Memon, Mahjabeen; Khemani, Vashdev; Raja, Riaz Ahmed (Journal of Liaquat University of Medical & Health Sciences, 2019)
(LBP) among the women of child bearing age attending Neurosurgery OPD, and to find the association between observing veil and vitamin D3 deficiency. METHODOLOGY: Cross-sectional study, conducted at Neurosurgery OPD, Civil Hospital, Hyderabad, Pakistan from December 2013 to May 2014. Questionnaires from 100 patients selected by Stratified random sampling of only Women of Child Bearing Age (15-49 years) having LBP of unknown cause were included. Vitamin D3 test reports were obtained. Software’s used were Microsoft Excel, SPSS version 16.0 and SPSS version 20.0. RESULTS: Out of 100 patients, 60 patients (60%) were Vitamin D3 deficient (0-20ng/ml), 23 patients (23%) were having Vitamin D3 insufficiency (20-30ng/ml) and those with Vitamin D sufficiency (30-100ng/ml) or efficiency (>100ng/ml) were only 15 patients (15%) and 2 patients (2%) respectively. Out of 60 females who were Vitamin D deficient, 49(81.7%) were observing veil (no adequate sunlight exposure) and 11 (18.3%) were without veil (well-exposed to sun) which was found to be statistically significant. CONCLUSION: Vitamin D3 deficiency or insufficiency is an associated risk factor for Idiopathic LBP, also observing veil can lead to significantly low vitamin D3 levels associated with high prevalence of LBP risk in women of child bearing age in otherwise sunny regions. Therefore, adequate vitamin D3 supplementation can be mandatory to prevent and treat LBP. This needs to be evaluated in further researches at a local level.